PEMBERDAYAAN MASYARAKAT MELALUI PROGRAM SESARENGAN NGOPENI KADANG KEKURANGAN DI DESA PILANG KECAMATAN RANDUBLATUNG - Nazelia Shoeladina; Retno Sunu Astuti; Amni Zarkasyi Rahman (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2023)
Pilang village is a village included in the classification of the poor population highest in Randublatung Subdistrict. The “program Sesarengan Ngopeni Kadang Kekurangan” in the Family Hope Program aims to reduce poverty. This research aims to analyze community empowerment “Program Sesarengan Ngopeni Kadang Kekurangan” in Pilang Village, Randublatung District, Blora Regency. The research method used is a descriptive qualitative approach with data collection techniques through interviews, observation, and documentation. This research uses the theory of Robert Chambert regarding the implementation of empowerment which includes improving education, improving life, improving income, improving society. The results showed that the implementation of empowerment in the PKH Program in improving education, improving life, social welfare, improving income, improving health has not been effective because there are still obstacles in its implementation. This is influenced by inhibiting factors such as the emergence of social jealousy in the community, the workload of PKH assistants does not match the number of beneficiaries who must be assisted, the behavior of beneficiaries who are not disciplined because they do not carry out their obligations, limiting the quota of KPM recipients. The recommendations given are to increase reading interest and school enrollment rates for KPM children, increase skills training for the elderly and disabled, increase entrepreneurial activities, increase Posyandu activities for pregnant women and toddlers.